The Effect of Post Operative Ketamine Nebulization on Post Operative Opioid Requirment in General Laproscopic Surgeries - Minahil Zaman, Shahryar, Ali Salman, Mehvish Saif, Muhammad Muazzam Butt, Hina Aslam (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The management of post-operative pain in patients undergoing laparoscopic surgery is crucial for early recovery and minimizing complications. The need for opioids to control pain is often significant, but opioid-related side effects, such as nausea, vomiting, and respiratory depression, remain a concern. This study investigates the potential of post-operative ketamine nebulization as an adjuvant to reduce opioid consumption in patients undergoing general laparoscopic surgeries. Methods: A total of 227 patients undergoing elective general laparoscopic surgeries were included in this randomized, controlled study. Patients were assigned to two groups: Group A (ketamine nebulization) and Group B (placebo nebulization). Ketamine nebulization was administered in the immediate post-operative period, with Group B receiving a saline nebulization. Post-operative opioid consumption, pain scores, and adverse effects were monitored at 6, 12, and 24 hours post-surgery. Results: The study showed a significant reduction in the total opioid consumption in the ketamine nebulization group compared to the placebo group (p < 0.05). Pain scores were also significantly lower in the ketamine group at all time points, with fewer patients reporting moderate to severe pain. Additionally, the ketamine group had a lower incidence of opioid-related side effects such as nausea and vomiting. Conclusion: Post-operative ketamine nebulization appears to be an effective strategy to reduce opioid requirements and improve pain management following general laparoscopic surgery. This approach may provide a valuable adjunct in post-operative analgesia, particularly in reducing the burden of opioid side effects. Keywords: Ketamine nebulization, opioid consumption, post-operative pain, laparoscopic surgery, opioid sparing, post-operative analgesia.